Island of the Blue Dolphins - O'Dell, Scott 1898-1989.; Lewin, Ted (Boston Houghton Mifflin, 1990)
Left alone on a beautiful but isolated island off the coast of California, a young Indian girl spends eighteen years, not only merely surviving through her enormous courage and self-reliance, but also finding a measure of happiness in her solitary life.
Keywords: Indians of North America -- Juvenile fiction; Indians of North America -- Fiction; Survival -- Fiction; Islands -- Fiction